2021
DOI: 10.3389/fcell.2021.673961
|View full text |Cite
|
Sign up to set email alerts
|

Protein Identification of Spermatozoa and Seminal Plasma in Bottlenose Dolphin (Tursiops truncatus)

Abstract: Proteins play an important role in many reproductive functions such as sperm maturation, sperm transit in the female genital tract or sperm-oocyte interaction. However, in general, little information concerning reproductive features is available in the case of aquatic animals. The present study aims to characterize the proteome of both spermatozoa and seminal plasma of bottlenose dolphins (Tursiops truncatus) as a model organism for cetaceans. Ejaculate samples were obtained from two trained dolphins housed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 137 publications
(168 reference statements)
0
6
0
Order By: Relevance
“…For example, a research group applied LC-MS/MS method to detect proteins from spermatozoa, and identified 419 in dolphin. More intriguingly, this group found that only 42 sperm proteins were common among humans, bovines, dogs, and dolphins ( Fuentes-Albero et al, 2021 ). For birds, 822 and 494 proteins were identified in sperm samples of chicken and zebra finches, respectively ( Labas et al, 2015 ; Rowe et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a research group applied LC-MS/MS method to detect proteins from spermatozoa, and identified 419 in dolphin. More intriguingly, this group found that only 42 sperm proteins were common among humans, bovines, dogs, and dolphins ( Fuentes-Albero et al, 2021 ). For birds, 822 and 494 proteins were identified in sperm samples of chicken and zebra finches, respectively ( Labas et al, 2015 ; Rowe et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The structural and functional integrity of spermatozoa is vital to male fertility. Proteins are considered major effectors of sperm function, which exert a crucial role in many reproductive functions, including sperm transport within the female tract and sperm-egg interaction ( Fuentes-Albero et al, 2021 ). Discrepancies in protein quality and quantity may cause an alteration in biological function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein constellation in spermatozoa and its respective compartments has been well documented using different proteomic-based techniques in a plethora of mammalian species [ 90 , 96 , 97 , 98 ]. Accordingly, differential expression patterns of certain families or types of sperm proteins following cryopreservation have been studied to estimate semen freezability [ 99 , 100 , 101 , 102 , 103 ].…”
Section: Protein Markersmentioning
confidence: 99%
“…Seminal plasma is a complex mixture of fluids from the testicle, epididymis, and accessory sex glands that includes components that affect sperm fertilization ability (Somashekar et al, 2015). Both the male and female reproductive characteristics of animals are significantly influenced by the complicated seminal plasma composition (Fuentes-Albero et al, 2021). In many species, seminal plasma proteins have been identified as fertility indicators (Yue et al, 2009;Kadoom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%